Association between socioeconomic status and incident stroke in China. Issue 6 (27th April 2020) - Zhou, Weiju; Chen, Ruoling; Hopkins, Alex; Wang, Yulong; Tang, Jie; Chen, Xiangyan; Clifford, Angela; Pan, Yuesong; Forthby, Ken; Ni, Jindong; Wang, Duolao; Brunner, Eric
Abstract : Background: Little is known about the impact of socioeconomic status (SES) on incidence of stroke in China. This study aimed to examine the association of SES, which was measured by different indicators, with incidence of stroke and gender differences in the association. Methods and results: Two prospective cohort studies were conducted including 2852 participants aged ≥60 years in Anhui province and 3016 participants in four other provinces in China. During a median follow-up of 7.1 years, 211 incident stroke cases occurred in the Anhui cohort. The risk of stroke increased with living in rural areas (adjusted HR 2.49, 95% CI 1.19 to 5.22; women 3.64, 95% CI 1.17 to 11.32, men 2.23, 95% CI 0.81 to 6.19), but not significantly with educational level, occupational class, satisfactory income and financial problems (except for women with low education). The four-province cohort had 113 incident stroke cases over the 3.1 years' follow-up. The five SES indicators were not significantly associated with incident stroke (except for increased risk in men with high occupation), but additional measurement for actual income showed that incident stroke increased in women with low personal income and in men with high family income. Pooled data from the two cohorts demonstrated the impacts of rural living (1.66, 95% CI 1.08 to 2.57) and having high occupational class (1.56, 95% CI 1.01 to 2.38), and gender differences for women with low education (2.26, 95% CI 1.19 to 4.27). Conclusions: Rural living and being female with low SES are associated with increased stroke risk in China. Strategies to improve public health in the rural communities and gender-specific targets for health inequality should be an integral component of stroke interventions.